Waste Management in Muang District, Samutprakarn Province, Thailand - Bunchinwutthikul, Sompit (Journal of Public Administration Chiang Rai Rajabhat University, 2021)
This research aimed to investigate the components of waste management (or waste disposal) in Muang district, Samutprakarn province, to analyze and compare the factors affecting its waste management in the Muang community with personal factors. Yamane formula was used as a tool to calculate the sample size on 95 percent confidence interval and 5 percent acceptable error or 0.05. The sample groups studied in this research were 376 residents living in this area. The questionnaire were used as a research instrument to collect data. Percentage, means, average percentage value of T-distribution, standard deviation (t-test), and F-distribution (F-test) were employed in statistical analysis. The results found that1) the level of waste management in Muang district, Samutprakarn province was very high; and 2) the factors of gender, education, occupation, household income, period of residents living in the community, and the number of household members affecting waste management were different at a statistically significant level of 0.05.